Analyse the property crime cases in Johor Bahru Utara using spatial analysis geographic information system / Siti Nurahin Ahmad - Ahmad, Siti Nurahin (2020)
The Johor Bahru is one of the sub-district in Johor is the third largest city in Malaysia with a people of 1.4 million and is predictable rose up to 2.2 million in year 2020 (Economic Report, 2005, 2006) that have a high number of crime cases. The aim of this research is to analyse property crime pattern and its relationship on population, labour force, metrological and built environment in Johor Bahru using Geographic Information System (GIS). Performed geocoding of the database is process to performed in order to locate the position of the crime cases on the map. Second process will proceed by open sources Quantum GIS (QGIS). Hot Spot Analysis using Kernel Density Estimation. The Kernel density estimation (KDE) is the most suitable spatial analysis technique for the hotspot crime cases. Last stage, the regression analysis using Ordinary Least Square (OSL) is performed in order to get the P-value which is the probability of the relationship and also derived the multiple R-squared and adjusted R-squared from the regression equation to quantify model performance. The result is Map of hotspot crime cases in Johor Bahru and what pattern is influence the Property Crime Cases based on relationship between factor and cases.